1985
DOI: 10.1128/aac.28.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Comparative single-dose pharmacokinetics of amantadine hydrochloride and rimantadine hydrochloride in young and elderly adults

Abstract: The single-dose pharmacokinetics of amantadine hydrochloride and rimantadine hydrochloride were compared in a randomized, two-period, crossover study involving six young (<35 years) and six elderly (.60 years) adults. Subjects ingested single 200-mg oral doses after an overnight fast, and serial plasma (0 to 96 h), nasal mucus (0 to 8 h), and urine (0 to 24 h) samples were collected for assay of drug concentration by electron capture gas chromatography. For both groups combined, rimantadine differed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
77
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 16 publications
1
77
1
Order By: Relevance
“…Only in time to Cmax did our study population differ from the younger adult population (2.5 and 1.9 h for the first and last doses, respectively, for our study population). The average time to Cmax of 4.0 h seen after a single 200-mg dose in elderly adults (9) is likewise longer than that observed in our study. In contrast to earlier studies, our study allowed volunteers to eat breakfast shortly after dosing.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Only in time to Cmax did our study population differ from the younger adult population (2.5 and 1.9 h for the first and last doses, respectively, for our study population). The average time to Cmax of 4.0 h seen after a single 200-mg dose in elderly adults (9) is likewise longer than that observed in our study. In contrast to earlier studies, our study allowed volunteers to eat breakfast shortly after dosing.…”
Section: Discussioncontrasting
confidence: 55%
“…However, this correlation has not been directly established. A previous study of rimantadine given at a single dose to volunteers suggested that rimantadine, unlike its relative, amantadine, may concentrate in respiratory secretions (9). In that short-term study (9) the ratio of concentration in nasal mucus to that in plasma peaked at 1.7 ± 1.1 (mean ± SD) at 8 h after administration.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations